1998
DOI: 10.1159/000052725
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vocalization in Species Differentiation of Sulawesi Tarsiers

Abstract: Recent work on the tarsiers of Sulawesi indicates that the degree of species differentiation is greater than has hitherto been thought. This is indicated by the acoustic differences between the vocal duets of mated pairs of Tarsius spectrum, Tarsius dianae and tarsiers from the Togian Islands (Tomini Bay, Sulawesi). This paper presents further evidence of taxonomic differentiation, based on the vocal behaviour shown during playback experiments. Six adult T. spectrum, kept in captivity, were stimulated by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 13 publications
(13 reference statements)
0
43
0
4
Order By: Relevance
“…Unimodal acoustic duets and temporally specific patterns of antiphonal calling by males and females have been described among some bushcrickets (Hartley et al, 1974;Heller and von Helversen, 1986;Robinson et al, 1986;Stumpner and Meyer, 2001;Bailey and Hammond, 2004), grasshoppers (von Helversen et al, 2004), mosquitos (Cator et al, 2009), flies (Donegan and Ewing, 1980), frogs (Tobias et al, 1998), mammals (Mitani, 1985;Nietsch, 1999) and birds (Thorpe et al, 1972). Unimodal vibratory courtship duets have likewise been described among spiders (Baurecht and Barth, 1992), planthoppers (Ichikawa, 1976), stoneflies (Ziegler and Stewart, 1977), stinkbugs (Cokl and Virant-Doberlet, 2003) and lacewings (Henry, 1980).…”
Section: Discussion a Novel Multimodal Duetting Systemmentioning
confidence: 99%
“…Unimodal acoustic duets and temporally specific patterns of antiphonal calling by males and females have been described among some bushcrickets (Hartley et al, 1974;Heller and von Helversen, 1986;Robinson et al, 1986;Stumpner and Meyer, 2001;Bailey and Hammond, 2004), grasshoppers (von Helversen et al, 2004), mosquitos (Cator et al, 2009), flies (Donegan and Ewing, 1980), frogs (Tobias et al, 1998), mammals (Mitani, 1985;Nietsch, 1999) and birds (Thorpe et al, 1972). Unimodal vibratory courtship duets have likewise been described among spiders (Baurecht and Barth, 1992), planthoppers (Ichikawa, 1976), stoneflies (Ziegler and Stewart, 1977), stinkbugs (Cokl and Virant-Doberlet, 2003) and lacewings (Henry, 1980).…”
Section: Discussion a Novel Multimodal Duetting Systemmentioning
confidence: 99%
“…The distribution maps of such species, prepared mainly from the descriptions of the locations found with the museum specimens, also remain crude. Longterm and detailed studies on species within primate groups including Tarsiiformes, Lemuriformes, Galaginae and Aoutidae have revealed that the actual numbers of these species are highly underestimated, which has led to wide-spread acceptance of newer species and/or subspecies and frequent taxonomic rearrangements (Masters 1988, Zimmermann et al 1988, Bearder et al 1995, Martin 1995, Hafen et al 1998, Nietsch 1999, Pastorini et al 2003, Nekaris & Jaffe 2007. Many of these species, formerly thought to be broadly distributed, are now considered to be confined to more restricted ranges (Ganzhorn et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Each of these forms came from a distinct biogeographic subregion of Sulawesi, and they interpreted this to indicate unrecognized taxonomic diversity. Niemitz (1984b) published a spectrogram of a tarsier from Gimpu (Central Sulawesi), which he identias T. t. pumilus, but which has since been shown to be the Palu acoustic form of MacKinnon and MacKinnon (1980), recently described as T. lariang Merker and Groves, 2006. work, Nietsch used acoustic evidence to argue for taxonomic separation of this population at the species level (Nietsch and Kopp 1988;Nietsch 1999), but did not name it. Shekelle et al (1997) found two more acoustic forms from Central Sulawesi and a third from North Sulawesi, bringing the total number of known acoustic forms at the time to seven.…”
Section: Taxonomic Historymentioning
confidence: 99%